The problems of classroom management facing the teachers of students with special needs in the Comprehensive Rehabilitation Center in Najran - Ali, Hanan Ibrahim Mohammed; Albashatwa, Rema Hussien Atawi (Journal of Educational and Psychological Sciences, 2019)
This study aims to explore the problems of classroom management facing the teachers of students with special needs in the Comprehensive Rehabilitation Center in Najran. The data were collected from number of (30) specialized teachers in the same Center. For data collection, questionnaire was developed by the researchers and the SPSS program was used for data analysis. Analysis of the study revealed that there were statistically significant differences for the benefit of the (B. A) Holders. Statistically significant differences were also shown in the variable of experience for the benefit of those who have been teaching for more than 6 years. The result also shown that that there were statistically significant differences for the variable of training to the benefit of those who attended (6) training courses or more. In the light of the results, a set of recommendations and proposals were presented to solve the problems and face their effects. (NU/SHED/13/118) تتقدم الباحثتان بالشكر لعمادة البحث العلمي بجامعة نجران على دعمها لهذا البحث برقم